2010
DOI: 10.1007/s00705-010-0814-x
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a revised taxonomy of the family Filoviridae: classification, names of taxa and viruses, and virus abbreviations

Abstract: The taxonomy of the family Filoviridae (marburgviruses and ebolaviruses) has changed several times since the discovery of its members, resulting in a plethora of species and virus names and abbreviations. The current taxonomy has only been partially accepted by most laboratory virologists. Confusion likely arose for several reasons: species names that consist of several words or which (should) contain diacritical marks, the current orthographic identity of species and virus names, and the similar pronunciation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
362
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(370 citation statements)
references
References 58 publications
1
362
1
6
Order By: Relevance
“…2 The genus Ebolavirus contains 5 known species: Bundibugyo (BDBV), Reston (RESTV), Sudan (SUDV), Ta€ ı Forest (TAFV) and Zaire ebolavirus (ZEBOV). 3 The current outbreak is associated with ZEBOV. 4 Four Ebolavirus species cause EHF in human, with the sole exception being RESTV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The genus Ebolavirus contains 5 known species: Bundibugyo (BDBV), Reston (RESTV), Sudan (SUDV), Ta€ ı Forest (TAFV) and Zaire ebolavirus (ZEBOV). 3 The current outbreak is associated with ZEBOV. 4 Four Ebolavirus species cause EHF in human, with the sole exception being RESTV.…”
Section: Introductionmentioning
confidence: 99%
“…5 Ebolavirus belongs to the order Mononegavirales and the family Filoviridae. 3 Its RNA genome encodes the following 7 protein products: Envelope glycoprotein (GP), Nucleoprotein (NP), RNA-dependent RNA polymerase L (L), Membrane-associated protein VP24 (VP24), Minor nucleoprotein VP30 (VP30), Polymerase cofactor VP35 (VP35), and Matrix protein VP40 (VP40). The GP transcript can be edited, 6 and the gene product can be processed by host protease, giving rise to 4 alternative forms of gene products: GP1,2; GP1,2delta; sGP and ssGP.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the genus Ebolavirus, the genus Marburgvirus contains a single virus species (Marburg marburgvirus), albeit consisting of two distinct viruses, Marburg virus and Ravn virus (2), which are approximately 20% divergent from one another (3). The filoviruses are primarily African in origin, with the exception of Reston virus, which so far has been found only in the Philippines or in nonhuman primates originating in the Philippines.…”
mentioning
confidence: 99%
“…1 The Marburgvirus genus currently includes a single viral species, Marburg marburgvirus, and 2 defined viruses, Marburg virus (MARV) and Ravn virus (RAVV). 1 The Ebolavirus genus includes 5 serologically distinct viral species: Zaire ebolavirus (EBOV), Sudan ebolavirus (SUDV), Reston ebolavirus (RESTV), Ta€ ı Forest virus (TAFV), and Bundibugyo ebolavirus (BDBV). The Cuevavirus genus has one viral species, Lloviu cuevavirus, and one defined virus, Lloviu virus (LLOV).…”
Section: Introductionmentioning
confidence: 99%
“…The Cuevavirus genus has one viral species, Lloviu cuevavirus, and one defined virus, Lloviu virus (LLOV). 1 Phylogenetic analysis of full-length genomic nucleotide sequences of viruses in each genus revealed that they have roughly similar identity to one another; i.e., MARV:EBOV ( 50%); MARV:LLOV (56%); EBOV:LLOV (51%). 1 MARV and all of the viruses in the Ebolavirus genus except Reston virus have caused severe hemorrhagic fevers in humans characterized by fever, anorexia, diarrhea, hemorrhaging, and a classic petechial rash, which typically disseminates from the head to the entire body as infection progresses.…”
Section: Introductionmentioning
confidence: 99%